Vitamin D3 upregulated protein 1 deficiency promotes N-methyl-N-nitrosourea and Helicobacter pylori-induced gastric carcinogenesis in mice. Issue 1 (13th September 2011) - Kwon, Hyo-Jung; Won, Young-Suk; Nam, Ki-Taek; Yoon, Yeo-Dae; Jee, Hyang; Yoon, Won-Kee; Nam, Ki-Hoan; Kang, Jong-Soon; Han, Sang-Uk; Choi, In-Pyo; Kim, Dae-Yong; Kim, Hyoung-Chin
Abstract : Objective: Vitamin D3 upregulated protein 1 (VDUP1) is a potent tumour suppressor whose expression is dramatically reduced in various types of human cancers, including gastric cancer. However, the precise mechanisms underlying tumour development remain unclear. In the present study, the authors examined the effect of VDUP1 on Helicobacter pylori -induced gastric carcinogenesis in mice. Design: Gastric cancer was generated in VDUP1 knockout (KO) and wild-type mice using a combination of N -methyl- N -nitrosourea treatment and H pylori infection. Fifty weeks after treatment, gastric tissues from both types of mice were examined by histopathology, immunohistochemistry and immunoblotting. In vitro tests on the human gastric cancer cell line, AGS, were also performed to identify the underlying mechanisms of cancer development. Results: The overall incidence of gastric cancer was significantly higher in VDUP1 KO mice than in wild-type mice. Similarly, VDUP1 KO mice showed more severe chronic gastritis, glandular atrophy, foveolar hyperplasia, metaplasia and dysplasia. Although no differences in the apoptotic index were apparent, lack of VDUP1 increased the rate of gastric epithelial cell proliferation in non-cancerous stomachs, with corresponding increases in tumour necrosis factor alpha (TNFα) level, nuclear transcription factor kappa B (NF-κB) activation and cyclooxygenase-2 (COX-2) expression. An in vitro study showed that H pylori -associated cell proliferation and induction of TNFα, NF-κB and COX-2 were inhibited in cells transfected with VDUP1. In addition, overexpression of VDUP1 in AGS cells suppressed TNFα-induced NF-κB activation and COX-2 expression. Conclusion: Our data show that VDUP1 negatively regulates H pylori -associated gastric carcinogenesis, in part by disrupting cell growth and inhibiting the induction of TNFα, NF-κB and COX-2. These findings provide important insights into the role of VDUP1 in H pylori -associated tumourigenesis.